Ceramic tile preparation method and ceramic tile

By adding soda ash during the ball milling process to modify the raw ore bentonite, the problem of deteriorating mud performance caused by the use of a large amount of raw ore bentonite is solved, and a significant increase in the strength of ceramic green bodies and the improvement of kiln production capacity is achieved.

CN116924786BActive Publication Date: 2025-04-08DONGGUAN CITY WONDERFUL CERAMICS IND PARK +4
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310869470.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-04-08
Estimated Expiration
2043-07-14

AI Technical Summary

Technical Problem

In the prior art, if a large amount of raw ore bentonite is used to increase the strength of ceramic green bodies, it will lead to the problem of deterioration of mud performance.

Method used

Soda ash is added during the ball milling process to modify the raw ore bentonite in the blank formulation. Soda ash is added to the ball mill before stopping the ball to avoid damage to the modified bentonite structure by too long grinding time.

Benefits of technology

It significantly improves the strength of the green ceramics, and does not require a large amount of raw ore bentonite, avoids the problem of deterioration of mud performance, and improves the kiln production capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116924786B_ABST
    Figure CN116924786B_ABST
Patent Text Reader

Abstract

The present invention provides a ceramic tile preparation method and ceramic tile, the ceramic tile preparation method comprising: mixing raw materials in a blank formula according to a predetermined ratio to obtain a mixture, wherein the raw materials in the blank formula include raw bentonite; performing a first ball milling treatment on the mixture to obtain a first mud; adding soda ash to the first mud and performing a second ball milling treatment to obtain a second mud; drying and granulating the second mud to obtain a powder, performing a compression molding treatment on the powder to obtain a green body, and the green body is treated to obtain a ceramic tile. The present invention modifies the raw bentonite in the blank formula by adding soda ash during the ball milling process, and the soda ash is added to the ball mill before stopping the ball mill instead of being added with other raw materials when feeding, so as to avoid a long grinding time to reduce the damage to the structure of the modified bentonite, and the effect of significantly improving the strength of the green body can be achieved without adding a large amount of raw bentonite, thereby avoiding the problem of poor mud performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic tiles, and in particular to a method for preparing ceramic tiles and the ceramic tiles. Background Art

[0002] Ceramic production is a highly energy-intensive industry. It's reported that approximately 61% of the industry's energy consumption is used in the firing process, and 20% in the drying process. One very effective way to improve energy efficiency is to increase kiln capacity. The performance of the billet plays a significant role in increasing kiln capacity, and increasing kiln capacity places very high demands on the billet's performance.

[0003] The most direct way to increase kiln production capacity is to shorten the firing time. However, shortening the firing time greatly increases the risk of black heart in the product. Therefore, in order to significantly increase production capacity, improving the black heart condition of the blank becomes an urgent need. The main way to improve the black heart condition of the blank is to significantly reduce the amount of mud (clay) in the blank formula. Mud is the main raw material that provides strength to the blank. Currently, ceramic tile production generally adjusts the blank formula by using raw bentonite instead of mud to ensure green strength.

[0004] However, in order not to reduce the strength of the blank, a large amount of raw bentonite must be used to balance the strength loss caused by mud reduction. As the mud content decreases, the amount of raw bentonite used needs to be greatly increased. Since the aluminum content of raw bentonite is significantly lower than that of the mud, the aluminum content of raw bentonite is generally 15-18%, and the aluminum content of the mud is generally above 23%, and its degumming performance is very poor. If the amount of raw bentonite is too large (more than 8%), the mud performance will be significantly deteriorated, which is not conducive to the screening and transportation of the mud. At the same time, the aluminum content in the blank formula is difficult to guarantee.

[0005] Therefore, the existing technology has defects and needs to be improved and developed. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a ceramic tile preparation method and ceramic tile in response to the above-mentioned defects of the prior art, aiming to solve the problem in the prior art that if a large amount of raw bentonite is used to improve the strength of ceramic green bodies, the mud performance will deteriorate.

[0007] The technical solutions adopted by the present invention to solve the technical problems are as follows:

[0008] A method for preparing ceramic tiles, comprising:

[0009] The raw materials in the blank formula are mixed according to a predetermined ratio to obtain a mixture, wherein the raw materials in the blank formula include raw bentonite;

[0010] performing a first ball milling process on the mixture to obtain a first slurry;

[0011] adding soda ash to the first slurry and then performing a second ball milling process to obtain a second slurry;

[0012] The second slurry is dried and granulated to obtain a powder, the powder is pressed and molded to obtain a green body, and the green body is processed to obtain a ceramic tile.

[0013] According to the above technical means, the embodiment of the present application modifies the raw bentonite in the billet formula by adding soda ash during the ball milling process, and the soda ash is added to the ball mill before stopping the ball instead of being added when adding other raw materials, thereby avoiding excessive grinding time to reduce damage to the modified bentonite structure, and can significantly improve the green body strength. The effect of significantly improving the green body strength can be achieved without adding a large amount of raw bentonite, thereby avoiding the problem of deterioration of mud performance.

[0014] In one implementation, the mass fraction of the raw bentonite accounts for 5-8% of all raw materials in the blank formulation.

[0015] According to the above technical means, the embodiment of the present application can achieve the purpose of improving the strength of the ceramic green body without using too much amount, avoiding the problem of poor mud performance caused by excessive use of raw bentonite.

[0016] In one implementation, the amount of soda ash added is 3% by mass of the raw bentonite.

[0017] According to the above technical means, the embodiment of the present application only needs to use 5-8% of raw bentonite, and then add 3% of the raw bentonite dry material amount in the formula of soda ash to modify the raw bentonite with soda ash, so that the strength of the blank can be greatly improved. At the same time, since the amount of raw bentonite does not need to be too large, the mud performance is basically unaffected, which greatly improves the flexibility of formula adjustment.

[0018] In one implementation, the chemical composition of the raw bentonite includes, by mass percentage:

[0019] Loss on ignition 0~6%, SiO2 69~74%; Al2O3 16.5~19%; Fe2O3 0~1.5%, CaO+MgO0~1.0%, K2O+Na2O 0~3%.

[0020] According to the above technical means, the embodiment of the present application uses the above raw bentonite to replace part of the clay, thereby improving the strength of the ceramic green body.

[0021] In one implementation, the raw materials in the blank formulation include, by mass percentage:

[0022] Sodium ore powder 30%, white mud 15%, potassium sodium ore powder 6.5%, ceramic waste 5.5%, raw bentonite 7%, potassium sand 31.5%, magnesia 4.5%.

[0023] According to the above technical means, the amount of raw bentonite used in the embodiment of the present application is not large, and the mud performance is basically unaffected. It is possible to improve the strength of the ceramic green body without affecting normal production, thereby achieving the effect of increasing the kiln production capacity.

[0024] In one implementation, before the mixed material is subjected to a first ball milling process to obtain a first slurry, the process further includes:

[0025] Determine the total grinding time based on the predetermined slurry fineness screening standard;

[0026] A second grinding time is predetermined, and the difference between the total grinding time and the second grinding time is used as the first grinding time.

[0027] According to the above technical means, in the embodiment of the present application, soda ash is added before the ball milling is completed, thereby avoiding excessively long milling time and reducing damage to the structure of the modified bentonite.

[0028] In one implementation, the mixed material is subjected to a first ball milling process to obtain a first slurry, comprising:

[0029] The mixture is subjected to a first ball milling, and when a first milling time is reached, the first ball milling is stopped to obtain a first slurry.

[0030] According to the above-mentioned technical means, the embodiment of the present application divides the ball milling process into the first ball milling and the second ball milling, and realizes the addition of soda ash during the ball milling process to modify the raw bentonite in the formula, so that the strength of the ceramic tile green body can be improved without adding a large amount of raw bentonite, and the performance of the mud will not be affected.

[0031] In one implementation, adding soda ash to the first slurry and then performing a second ball milling process to obtain a second slurry comprises:

[0032] adding soda ash to the first slurry and then performing a second ball milling; when the predetermined second milling time is reached, stopping the second ball milling to obtain a second slurry;

[0033] The second grinding time is 0.5 to 1.5 hours.

[0034] According to the above technical means, in the embodiment of the present application, adding soda ash 0.5 to 1.5 hours before stopping the ball has little effect on the mud performance.

[0035] In one implementation, the strength of the raw bentonite is greater than or equal to 4.5 MPa.

[0036] According to the above technical means, the embodiment of the present application selects raw bentonite with a single test strength greater than or equal to 4.5 MPa, so that the strength of the ceramic green body is improved after adding raw bentonite to the raw materials.

[0037] The present invention discloses a ceramic tile, wherein the ceramic tile is prepared by the ceramic tile preparation method described above.

[0038] The present invention achieves the following beneficial effects:

[0039] (1) By using 3% of the original bentonite dosage, sodium carbonate is added to the mud 0.5 to 1.5 hours before stopping the ball, which plays a role in modifying the original bentonite in the formula. + Ion replacement of Ca in bentonite 2+ ions, the adsorption is greatly increased, thereby improving the green strength;

[0040] (2) Add it 0.5 to 1.5 hours before stopping the ball, and avoid grinding for too long to reduce the damage to the structure of the modified bentonite, which will have a better effect;

[0041] (3) Raw bentonite is widely available and can be directly used in the formulation like other raw materials without being processed before being added. It is not necessary to use too much raw bentonite in the formulation to obtain a higher green strength, thereby reducing the occurrence of green cracking defects. At the same time, it reduces the impact of raw bentonite on mud properties, and the flexibility of formula adjustment is also improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a flow chart of a preferred embodiment of the method for preparing ceramic tiles of the present invention. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the present invention more clear and distinct, the present invention is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0044] Reducing energy consumption and improving energy efficiency are long-standing goals in the ceramics industry, and increasing kiln capacity is a key measure to achieve this goal. To increase capacity, the black core of the blanks must be improved during firing. This improvement is primarily achieved by reducing the amount of mud (clay) used in the blanks. Raw bentonite generally has a low aluminum content and is difficult to debond. Adding too little to the formula will result in substandard green strength, while adding too much will likely result in a difficult-to-reach aluminum content and poor mud properties, making debonding difficult.

[0045] To address the above-mentioned drawbacks, the present invention provides a method for preparing a ceramic tile and a ceramic tile. The method comprises: mixing raw materials in a blank formulation according to predetermined proportions to obtain a mixture, wherein the raw materials in the blank formulation include raw bentonite; subjecting the mixture to a first ball milling process to obtain a first slurry; adding soda ash to the first slurry and subjecting the mixture to a second ball milling process to obtain a second slurry; drying and granulating the second slurry to obtain a powder; subjecting the powder to a press-molding process to obtain a green body; and subjecting the green body to processing to obtain a ceramic tile. The present invention modifies the raw bentonite in the blank formulation by adding soda ash during the ball milling process. Furthermore, the soda ash is added to the ball mill before the ball mill is stopped, rather than being added with other raw materials at the time of feeding, thereby avoiding excessive grinding time and thus reducing damage to the modified bentonite structure. The green body strength can be significantly improved without adding a large amount of raw bentonite, thereby avoiding the problem of deterioration in the slurry performance.

[0046] See Figure 1 , Figure 1 Flowchart of the method for preparing ceramic tiles of the present invention. Figure 1 As shown, the ceramic tile preparation method according to the embodiment of the present invention includes the following steps:

[0047] Step S100: mixing raw materials in a blank formula according to a predetermined ratio to obtain a mixture, wherein the raw materials in the blank formula include raw bentonite.

[0048] In this example, raw bentonite is used in the green body formulation to enhance the strength of the ceramic green body. Furthermore, 1.0% of the auxiliary material sodium silicate is added simultaneously during the batching process. Soda ash is not added at this point, but rather after a certain period of ball milling. This avoids prolonged milling and reduces damage to the modified bentonite structure, resulting in a more effective result.

[0049] In one embodiment, the mass fraction of the raw bentonite accounts for 5-8% of all raw materials in the blank formulation. This embodiment can improve the strength of the ceramic green body without using too much raw bentonite, avoiding the problem of poor mud performance caused by excessive use of raw bentonite.

[0050] In one implementation, the amount of soda ash added is 3% by mass of the raw bentonite. This embodiment requires only 5-8% of raw bentonite in the billet formulation, and by adding 3% of the raw bentonite dry material in the formulation to modify the raw bentonite with soda ash, the billet strength can be significantly improved. Furthermore, since the amount of raw bentonite does not need to be too large, the mud performance is essentially unaffected, and the flexibility of formula adjustment is greatly improved.

[0051] In one implementation, the chemical composition of the raw bentonite, measured by mass percentage, includes: loss on ignition 0-6%, SiO2 69-74%, Al2O3 16.5-19%, Fe2O3 0-1.5%, CaO+MgO 0-1.0%, and K2O+Na2O 0-3%, where the sum of the mass percentages of the individual chemical components is 100%. This embodiment uses the raw bentonite to replace part of the clay, thereby improving the strength of the ceramic green body.

[0052] In one embodiment, the raw materials in the blank formula include, by mass percentage, 30% sodium stone powder, 15% white mud, 6.5% potassium sodium stone powder, 5.5% ceramic waste, 7% raw bentonite, 31.5% potassium sand, and 4.5% magnesia.

[0053] In the blank formula of this embodiment, 7% of raw bentonite is used to replace part of the mud material, thereby improving the strength of the ceramic green body. At the same time, the amount used is not large and the mud performance is basically unaffected, thereby achieving the effect of improving the strength of the ceramic green body without affecting normal production, thereby achieving the effect of increasing the kiln production capacity.

[0054] In one embodiment, the process before step S200 includes: determining the total grinding time according to a predetermined mud fineness screening residue standard; predetermining a second grinding time, and using the difference between the total grinding time and the second grinding time as the first grinding time.

[0055] Specifically, if the slurry moisture content is controlled at 32-35%, the slurry viscosity is 40-90 seconds, the specific gravity is 1.7-1.75, the ball mill load is 27 tons, and the predetermined slurry fineness residue is 2.0-2.4% (325 mesh sieve inlet), the total grinding time can be determined to be 12 hours, and the second grinding time can be determined to be 0.5-1.5 hours. For example, if the second grinding time is 1 hour, the second grinding time is 11 hours, indicating that the first grinding is stopped after 11 hours, and the second grinding is performed after adding soda ash.

[0056] like Figure 1 As shown, the ceramic tile preparation method according to the embodiment of the present invention further includes the following steps:

[0057] Step S200: performing a first ball milling process on the mixed material to obtain a first slurry.

[0058] In this embodiment, during ball milling, water is added to the mixed material in a ratio of dry material to water = 1:0.5, and the first ball milling process is performed.

[0059] In one implementation, the step S200 specifically includes: performing a first ball milling on the mixture, and when a first milling time is reached, stopping the first ball milling to obtain a first slurry.

[0060] In this embodiment, soda ash is added during the ball milling process, and the ball milling process is divided into the first ball milling and the second ball milling, thereby modifying the raw bentonite in the formula, so that the strength of the ceramic tile green body can be improved without adding a large amount of raw bentonite, and the performance of the mud will not be affected.

[0061] like Figure 1 As shown, the ceramic tile preparation method according to the embodiment of the present invention further includes the following steps:

[0062] Step S300: adding soda ash to the first slurry and performing a second ball milling process to obtain a second slurry.

[0063] In one embodiment, the step S300 specifically comprises: adding soda ash to the first slurry and performing a second ball milling; when the predetermined second milling time is reached, stopping the second ball milling to obtain a second slurry; the second milling time is 0.5 to 1.5 hours.

[0064] In this embodiment, soda ash is added to the mud 0.5 to 1.5 hours before the ball is stopped, thereby modifying the raw bentonite in the formula. If the bentonite is modified first and then added, the process is complicated and the raw bentonite is added after modification, resulting in a long grinding time for the modified raw bentonite, which affects the structure of the modified bentonite and the mud performance. Therefore, in this embodiment, adding soda ash 0.5 to 1.5 hours before the ball is stopped has little effect on the mud performance.

[0065] like Figure 1 As shown, the ceramic tile preparation method according to the embodiment of the present invention further includes the following steps:

[0066] Step S400: drying and granulating the second slurry to obtain powder, pressing and molding the powder to obtain green compacts, and processing the green compacts to obtain ceramic tiles.

[0067] This embodiment improves the strength of the ceramic green body, thereby shortening the firing time of the green body and preventing the green body from having a black core.

[0068] In one implementation, the raw bentonite has a strength greater than or equal to 4.5 MPa. In this embodiment, raw bentonite with a single-test strength greater than or equal to 4.5 MPa is selected (single-test strength refers to testing the bentonite strength alone, rather than testing the green body strength after adding it to the body formula). This allows the addition of raw bentonite to the raw materials to significantly improve the strength of the ceramic green body.

[0069] In this embodiment, a small amount of soda ash is used as an additive in the formula to modify the raw bentonite in the formula, and is added to the ball mill before the ball is stopped rather than added when other raw materials are added. This avoids excessive grinding time to reduce damage to the modified bentonite structure, which can significantly improve the green strength.

[0070] A specific embodiment is listed below for illustration.

[0071] The raw materials in the blank formulation, calculated by mass percentage, include: 30% sodium stone powder, 15% white clay, 6.5% potassium sodium stone powder, 5.5% ceramic waste, 7% raw bentonite, 31.5% potash sand, and 4.5% magnesia. The auxiliary material ratio is 1% sodium silicate and 0.21% soda ash. In other words, soda ash accounts for 3% of the bentonite in the blank formulation, or 0.07 x 0.03 = 0.21%.

[0072] The raw materials in the above blank formula are mixed according to the predetermined proportion, and water is added at the ratio of dry material: water = 1:0.5. The final mud moisture is controlled at 32-35%, the mud flow rate is 40-90 seconds, and the specific gravity is 1.7-1.75. At this time, only sodium silicate is added as auxiliary material, the ball mill loading capacity is 27 tons, and according to the mud fineness sieve residue control standard of 2.0-2.4% (325 mesh sieve import), it should be ground for 12 hours.

[0073] After grinding for 11 hours, stop grinding and take out the mud for later use. Then add 56 kg of soda ash (about 0.21%, accounting for 3% of the original bentonite amount). After adding the ball, grind for another hour until the fineness reaches the required 2.0-2.4% (325 mesh sieve import). At the same time, take out the mud after grinding with soda ash for later use.

[0074] The slurry before adding soda ash and the slurry after adding soda ash were dried and granulated respectively, and the granulation moisture was controlled at 7-8%. The slurry was pressed into small bricks (mould size 65×150 mm) using a SY60 small press. The small bricks were placed in an oven and baked at 150 degrees for 2 hours and then taken out. The strength was then tested using a DPK-A-500 flexural tester. During the test, the samples before and after adding soda ash were tested alternately in sequence to prevent the cooling time difference from interfering with the results. Four small bricks were pressed for each of the two schemes and the average strength test value was taken. The results are shown in Table 1.

[0075] Table 1 Modulus of rupture of samples before and after adding soda ash (unit: MPa)

[0076]

[0077] As can be seen from Table 1, the green strength of the slurry is significantly improved after adding soda ash. The method of improving the green strength of this embodiment can also be applied to different types of billet formulas, that is, adding soda ash at 3% of the amount of bentonite in the formula 1 hour before stopping the ball can significantly improve the green strength.

[0078] In the present invention, 3% of the raw bentonite is added to the mud 0.5 to 1.5 hours before the ball is stopped, so as to modify the raw bentonite in the formula. + Ions replace Ca in bentonite 2+ Ions, greatly increase the adsorption, thereby improving the green strength. Adding it 0.5 to 1.5 hours before stopping the ball, avoiding too long a grinding time to reduce damage to the modified bentonite structure, has better results. This method can be applied to various formulations. The process is simple, the raw bentonite is widely available, and it does not need to be processed before feeding and can be directly used in the formulation like other raw materials. It does not require too much raw bentonite in the formulation to obtain a high green strength, thereby reducing the occurrence of green cracking defects. At the same time, it reduces the impact of raw bentonite on mud properties, and the flexibility of formulation adjustment is also improved.

[0079] The present invention also discloses a ceramic tile, wherein the ceramic tile is prepared by the ceramic tile preparation method described above.

[0080] The present invention provides a method for preparing a ceramic tile and a ceramic tile. The method comprises: mixing raw materials in a blank formulation according to a predetermined ratio to obtain a mixture, wherein the raw materials in the blank formulation include raw bentonite; subjecting the mixture to a first ball milling process to obtain a first slurry; adding soda ash to the first slurry and subjecting the mixture to a second ball milling process to obtain a second slurry; drying and granulating the second slurry to obtain a powder; subjecting the powder to a press-molding process to obtain a green body; and subjecting the green body to processing to obtain a ceramic tile. The present invention modifies the raw bentonite in the blank formulation by adding soda ash during the ball milling process. Furthermore, the soda ash is added to the ball mill before the ball mill is stopped, rather than being added with other raw materials at the time of feeding, thereby avoiding excessive grinding time and thus reducing damage to the modified bentonite structure. The green body strength can be significantly improved without adding a large amount of raw bentonite, thereby avoiding the problem of deterioration of the slurry performance.

[0081] It should be understood that the application of the present invention is not limited to the above examples. For those skilled in the art, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a ceramic tile, characterized in that: include: The raw materials in the blank formula are mixed according to a predetermined ratio to obtain a mixed material, wherein the raw materials in the blank formula include raw bentonite; Performing a first ball milling process on the mixed material to obtain a first slurry; adding soda ash to the first slurry and then performing a second ball milling process to obtain a second slurry; Drying and granulating the second slurry to obtain powder, pressing and molding the powder to obtain green compacts, and processing the green compacts to obtain ceramic tiles; The mass fraction of the raw bentonite accounts for 5-8% of all the raw materials in the blank formula; The amount of soda ash added is calculated by mass fraction, accounting for 3% of the original bentonite; The chemical composition of the raw bentonite includes by mass percentage: Loss on ignition 0~6%, SiO2 69~74%; Al2O3 16.5~19%; Fe2O3 0~1.5%, CaO+MgO 0~1.0%, K2O+Na2O 0~3%; Before the mixed material is subjected to a first ball milling treatment to obtain a first slurry, the method further comprises: Determine the total grinding time according to the predetermined mud fineness screening standard; predetermining a second grinding time, and taking the difference between the total grinding time and the second grinding time as the first grinding time; Soda ash is added to the formula as an additive to modify the raw bentonite in the formula, improve the strength of the ceramic green body and shorten the firing time.

2. The method for preparing ceramic tiles according to claim 1, characterized in that: The raw materials in the blank formula include, by mass percentage: Sodium stone powder 30%, white mud 15%, potassium sodium stone powder 6.5%, ceramic waste 5.5%, raw bentonite 7%, potassium sand 31.5%, magnesia 4.5%.

3. The method for preparing ceramic tiles according to claim 1, characterized in that: The mixed material is subjected to a first ball milling process to obtain a first slurry, comprising: The mixed material is subjected to a first ball milling, and when a first grinding time is reached, the first ball milling is stopped to obtain a first slurry.

4. The method for preparing ceramic tiles according to claim 1, characterized in that: After adding soda ash to the first slurry, a second ball milling treatment is performed to obtain a second slurry, comprising: After adding soda ash to the first slurry, performing a second ball milling, and when a predetermined second grinding time is reached, stopping the second ball milling to obtain a second slurry; The second grinding time is 0.5 to 1.5 hours.

5. The method for preparing ceramic tiles according to claim 1, characterized in that: The strength of the raw bentonite is greater than or equal to 4.5 MPa.

6. A ceramic tile, characterized in that: The ceramic tile is prepared by the ceramic tile preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of fast-fired ceramic tile and product of fast-fired ceramic tile

    CN113248240A